Should Environmental Law Learn from Animal Law? Compassion as a Guiding Principle for International Environmental Law Instead of Sustainable Development - Tremblay-Huet, Sabrina (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2018)
Environmental law and animal law share many common elements and goals, but also exhibit many fundamental differences. Generally, conversations about the two are primarily concerned with what animal law can learn from environmental law. However, if one accepts the argument that environmental law needs to be, at the very least, reformed in order to afford real protection to the environment, or even revolutionized, then perhaps environmental law can also learn from animal law. What would the main lesson be? I argue that a turn to compassion, rather than sustainable development, as a guiding principle for international environmental law and its related scholarly discourse could be one of the main contributions offered by animal law. To illustrate this argument, I first present ecofeminist animal theory’s critique of the environmental movement. I expose the problematic nature of the concept of “sustainable development”, from an ecofeminist standpoint. I then use ecofeminist animal theorist Deane Curtin’s compassionate practice framework to develop the idea that another guiding principle for international environmental law must be adopted, drawing also on other contributions from ecofeminist animal theorists. Finally, I demonstrate how a compassionate guiding principle is already present in different animal law instruments, using examples of existing international legal norms on animal welfare, and insisting on the theme of the recognition of non-human animals as relational individuals.